`I now have so many friends!’ how young migrants describe their quest to belong in a town in southern Uganda - Janet Seeley; Rachel Kawuma; Edward Tumwesige; Allen Asiimwe; Chloe Lanyon; Sarah Bernays (International Journal of Adolescence and Youth, 2023)
ABSTRACTFor many young people in Uganda, labour migration has become a part of growing up. They may not move far, but it is still a move away from a place they belong. For young migrants, the route to economic independence may be precarious, even for those who have people they know nearby. We trace the experience of 12 young male and female migrants (aged 17–24 years) over their first year as a migrant in southern Uganda. Finding friends who could help find jobs, lend them money and be around to relax with, fulfiled an expressed need to belong. That friendship was often based on a shared interest in sport or through their place of work. In a setting where all the young people had at some point experienced hunger, insecurity and a fear of failing to make it, those friendships were a marker of beginning to feel they belonged.